Aloe Vera: A Wonder Plant with Multiple Activities - Akash Avhad; Suraj Aher; Shubham Hire; Dr. Gokul Talele (Asian Journal of Pharmaceutical Research and Development, 2024)
The medicinal properties of aloe vera, a drought-resistant succulent perennial, are widely recognized. Aloe vera has a multitude of well-documented health benefits, including immunomodulatory, hypoglycemic, anticancer, gastro-protective, antifungal, and anti-inflammatory qualities. It also aids in wound and burn healing. Aloe vera's advantageous therapeutic qualities have been used in a variety of commercial applications. In addition to providing an overview of its use in foods and cosmetics, the current study surveys the literature on its composition, rheology, processing, and pharmacological applications. Furthermore, a summary of the risks related to Aloe vera use is provided, along with pertinent safety measures. Scientific advancements in analytical chemistry are advancing the chemical characterization of Aloe vera.